2021
DOI: 10.1177/10870547211027647
|View full text |Cite
|
Sign up to set email alerts
|

Two Facets of Emotion Dysregulation Are Core Symptomatic Domains in Adult ADHD: Results from the SR-WRAADDS, a Broad Symptom Self-Report Questionnaire

Abstract: Objectives: Emotional dysregulation (ED) in adult ADHD is frequent but definition and tools for its evaluation are not consensual. Our aim was to determine the core ADHD symptomatic domains via the Self-Reported Wender-Reimherr Adult Attention Deficit Disorder Scale (SR-WRAADDS) following its validation in a large clinical sample of adults with ADHD and controls. Method: Three hundred sixty-nine adult patients with ADHD and 251 healthy participants completed the SR-WRAADDS and questionnaires about ADHD, depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
4
9
0
Order By: Relevance
“…The scale used in the present study also includes three other domains of symptoms associated with ADHD, namely oppositional symptoms, academic problems, and social attitudes. The psychometric properties of the SR-WRAADDS support its use in research and clinical practice ( 47 , 48 , 56 , 57 ). The SR-WRAADDS showed high correlations with the WRAADDS in an ADHD sample and every domain demonstrated discriminatory validity comparing adults with ADHD with healthy controls ( 47 ).…”
Section: Methodsmentioning
confidence: 87%
“…The scale used in the present study also includes three other domains of symptoms associated with ADHD, namely oppositional symptoms, academic problems, and social attitudes. The psychometric properties of the SR-WRAADDS support its use in research and clinical practice ( 47 , 48 , 56 , 57 ). The SR-WRAADDS showed high correlations with the WRAADDS in an ADHD sample and every domain demonstrated discriminatory validity comparing adults with ADHD with healthy controls ( 47 ).…”
Section: Methodsmentioning
confidence: 87%
“…Finally, while we focused in this review on racing thoughts only, we should mention that other psychological dimensions related to racing thoughts might also be found in both BD and ADHD. For instance, emotional dysregulation is not included among the diagnostic criteria of ADHD nor BD 11 but it is a core symptomatic domain in adult ADHD 68 and BD. Interestingly, comparative studies have reported that in euthymic patients with BD, emotion responsiveness is higher than in controls but lower than in patients with ADHD, whereas emotion lability does not differ between the two clinical groups.…”
Section: Discussionmentioning
confidence: 99%
“…To study ED, in particular emotional lability in ADHD, we were interested in the cyclothymic temperament subscale of the TEMPS-A. All the scales used were self-reported and validated in French (113)(114)(115)(116)(117) with Likert scales to consider the frequency of symptoms.…”
Section: Questionnairesmentioning
confidence: 99%